2003
DOI: 10.1074/jbc.m307700200
|View full text |Cite
|
Sign up to set email alerts
|

Compartment-specific Protection of Iron-Sulfur Proteins by Superoxide Dismutase

Abstract: Iron and oxygen are essential but potentially toxic constituents of most organisms, and their transport is meticulously regulated both at the cellular and systemic levels. Compartmentalization may be a homeostatic mechanism for isolating these biological reactants in cells. To investigate this hypothesis, we have undertaken a genetic analysis of the interaction between iron and oxygen metabolism in Drosophila. We show that Drosophila iron regulatory protein-1 (IRP1) registers cytosolic iron and oxidative stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 45 publications
2
85
0
Order By: Relevance
“…6B). Separation of cellular aconitase activities by electrophoresis (10,31) confirmed that the modest increase in total activity was due to specific increase from the overexpressed cytosolic aconitases (Fig. 6C).…”
Section: Expression and Purification Of Recombinant Irp-1a And Irp-1b-mentioning
confidence: 66%
See 1 more Smart Citation
“…6B). Separation of cellular aconitase activities by electrophoresis (10,31) confirmed that the modest increase in total activity was due to specific increase from the overexpressed cytosolic aconitases (Fig. 6C).…”
Section: Expression and Purification Of Recombinant Irp-1a And Irp-1b-mentioning
confidence: 66%
“…Together with an alternatively spliced transcript of the ferritin 1 heavy chain homolog (Fer1HCH), these are the only two genes in the Drosophila genome that were shown to possess an IRE (28 -30). Although electrophoretic analysis of fly extracts suggests the presence of a single protein binding to IRE and a single protein possessing cytosolic aconitase activity (31), Drosophila actually contains two highly homologous IRP1-like proteins (IRP-1A and IRP-1B) encoded by different genes (17,32). Herein, we have purified heterologously expressed IRP-1A, IRP-1B, and hybrid IRP-1A/IRP-1B proteins and determined that although both IRPs are functional aconitases, only IRP-1A binds IREs.…”
mentioning
confidence: 99%
“…The aconitases are subject to reversible inactivation by ROS (38,39). The vulnerability of the solvent-exposed Fe-S cluster of the these enzymes to ROS attack provides a sensitive indicator of changes in ROS flux in vivo (38,39).…”
Section: Resultsmentioning
confidence: 99%
“…The aconitases are subject to reversible inactivation by ROS (38,39). The vulnerability of the solvent-exposed Fe-S cluster of the these enzymes to ROS attack provides a sensitive indicator of changes in ROS flux in vivo (38,39). To determine further whether ectopically expressed CAT actually reduces the ROS burden in DFH-deficient flies, we used the activities of mACON and cytoplasmic aconitase (cACON) to assess the level of ROS flux in DFH-deficient flies expressing mitoCAT.…”
Section: Resultsmentioning
confidence: 99%
“…However, recent studies in Drosophila lacking SOD1 revealed an increase in IRP1 RNA binding activity, suggesting an ability of O 2 À to promote complete loss of the [4Fe-4S] (Missirlis et al, 2003). An equally plausible scenario is that O 2 À also interferes with the pathway of cytosolic Fe-S assembly.…”
Section: Discussionmentioning
confidence: 99%